Reproductive biology of the shrimp Palaemon northropi (Rankin, 1898) (Caridea: Palaemonidae) from an estuary in the Brazilian northeastern - Barros-Alves, Samara de Paiva; Tupy, Gabriela Santos; Almeida, Andréa Santos; dos Santos, Mariel Salvador; Alves, Douglas Fernandes Rodrigues (Scientia Plena, 2019)
The objective of this study was to evaluate aspects of the reproductive biology of Palaemon northropi, a shrimp of the northeastern Brazilian estuarine region. The specimens were sampled between July and November 2017, with a hand net, and were identified to species level and sexed. We measured the carapace length (CL) of males and females and the second pleura length (PL) of females. A total of 85 individuals were collected, including 36 males and 49 females (24 non-ovigerous and 25 ovigerous). The sex ratio was 0.42, with a non-significant departure from the 1:1 ratio. Mean sizes (±SD) of males and females were 3.41±0.54 and 4.98±1.33 mm CL, respectively. The mean size of the PL (±SD) of females was 2.67±1.03 mm CL. Mean fecundity was 255±57.84 embryos. The CL was positively associated with fecundity, but the fecundity did not vary between embryo developmental stages. Palaemon northropi shows sexual dimorphism, with females being larger than males. The results indicate that the embryonic development of P. northropi occurs normally, even in an estuarine region, such as that of present study, since there was no significant loss of embryos during development. This study contributes to knowledge of the reproductive biology of P. northropi and help in our understanding of the ecological relevance of these shrimps in estuarine environments.